MODIFIKASI GIGI MANUSIA BINANGUN DAN LERAN: Â€ŒTEMUAN BARU DI KAWASAN PANTAI UTARA KABUPATEN REMBANG, JAWA TENGAHÂ€ - Kasnowihardjo, Gunadi; Suriyanto, Rusyad Adi; Koesbardiati, Toetik; Murti, Delta Bayu (BRIN, 2013)
Something interesting about the findings of the human skeleton in Binangun and Leran Prehistoric Burial Sites is the modification of the human teeth that is extremely rare found in prehistoric grave in Java as well as in Indonesia. Such tradition is still practiced in Java and Bali by leveling the top or bottom front teeth (Jawa: pangur tradition). Forms of human teeth of Binangun, Leran 1 and Leran 2 are very unique, teeth of Binangun is tapered while human teeth of Leran 1 and Leran 2 shaped like a flower bud. Anatomically the shape of teeth can be altered by a person in the habit of using his teeth. But variations in tooth shape as found in individuals in the Binangun and Leran sites, Rembang regency, Central Java province, in general is the result of a tribal culture.